Cobalt Ferrite Nano-composites for the oxidation of Phenols in oil refinery wastewater - Mohamed, Amira (AUC Knowledge Fountain, 2022)
Phenolic compounds have the tendency to persist in the environment over a long period making them a main source of concern because of their toxic characteristics towards humans and animals (Bruce et al., 1987). Therefore, existence of phenolic compounds in aquatic environment is unfavourable and as a result, many treatment techniques have been implemented to treat the wastewater produced from petroleum refineries. Petroleum refineries are among the top industries that produces significant quantities of high phenol concentration wastewater. Photo-catalysis is a promising and effective method to treat phenol present in oil refineries effluent. In this study, the photo-catalyst used is recommended to be in the Nano size in order to provide better dispersion leading to higher phenol degradation. Because the effect of disposing Nano sized particles to the environment is still unclear and the nano-composites are expensive materials. In this study, magnetic recovery of the particles was taken into consideration. Accordingly, this study aims to test the performance of a synthesized magnetically recoverable nano-composite catalyst and its removal efficiency of phenols at different operating conditions and examine its recoverability. The first phase of this study focused on catalyst synthesis and its characterization. The composite nano-particles obtained showed a successful formation of cobalt ferrite core surrounded by titanium dioxide shell, with an average size 65.5nm, and super paramagnetic properties. The second phase of the study aimed to determine the optimum operating parameters for a batch reactor including catalyst dosage, initial pH, and induced aeration corresponding to different initial phenol concentration. It was noticed that the CNP dosage varies between 0.5 g/l to 2 g/l according to initial phenol concentration and initial pH, an initial pH of 3 showed the highest degradation rates for different initial phenol concentration, and Aeration proved to have a major effect on the removal efficiency of phenol. Second phase also discussed the recovery of the catalyst as well as the possibility of its sequential reuse. It was noticed that CNP degradation ability decreased within a range of 5% during five cycles of reuse. The third phase of this study tested the optimum operating conditions obtained from the second phase on a continuous flow reactor in order to pave the road for future upscale applications. This showed a slight decrease in removal efficiency due to the physical difficulty in connecting the air pump to the reactor.